Research Integrity Risk Index (Ri²): A Critical Evaluation Review - Abdulwahid, Dhurgham A; Abed, Alaa H. (American Journal of Biomedicine and Pharmacy, 2025)
Background: RI2 is a newly founded measure, designed to assess the research integrity in the world universities. This measure is based on two indicators; these are the published-research retraction rate and the rate of researches published in journals that have been delisted from Scopus and Web of Science indexes. The measure is characterized by its reliance on verifiable references including monitoring the number of retracted published studies, which enables the universities and other research relevant bodies to diagnose any research integrity concerns. This means that RI² is a mixed quantitative-qualitative measure. Purpose: This paper aims at evaluating RI² via analyzing its systematic methodology, data accuracy, transparency, and effectiveness. Method: The study was conducted through reviewing the available relevant literature, including the RI2 evaluation process mechanisms. Results: Although the approaches followed by the measure were qualitative quantitative, there are some criticisms that need to be solved to improve the performance of the measure. Conclusions: Caution is warranted, as research retraction rates can have different implications and may be indicative of high levels of monitoring and oversight rather than misconduct. Moreover, issues such as incomplete metadata and methodological decisions can influence results. Recommendations: It is argued that improving normalization methods and data quality would enhance RI²’s fairness and reliability.